KETUPAT AS A TRADITIONAL INDONESIAN CULTURAL FOOD - Aliyah Nur Rahmah; A. Afwan Azimi; Kiara Indri Barokah; Sinta Maulidia Azzahra (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
Indonesia is an archipelago nation with a diverse population of racial and cultural backgrounds. This makes Indonesians rich in expression culture, considered valuable, and plays an important role in representing the self-nation of Indonesia. Culture is very tightly related to religion. The majority of Indonesians are Muslims; therefore, Indonesia has the largest Muslim population in the world. Religion and culture are closely related; one example is the Indonesian custom of eating ketupat on Eid Al-Fitr. Ketupat is made from two plant-derived ingredients: coconut leaves as a wrapper and sticky rice as the main ingredient. Young coconut leaves have become the identity of the ketupat because they are used to wrap the contents of the ketupat by forming specific shapes, for example, diamonds. Sunan Kalijaga, an Indonesian theologian and significant figure for Muslims in Java, is credited with introducing ketupat to the region. However, over time, the custom of eating ketupat exclusively during Eid Al-Fitr will fade. Every Indonesian region started to develop a unique culture for making and serving ketupat.